(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Observations are reported on infestations of the snoutbeetle Sphenophorus striatopunctatus Goeze that took place in experimental plots of microthermic grasses used for turf composition. Of the tested 110 varieties of the genus Festuca, of Lotium perenne, and of Poa pratensis, only the 20 P. pratensis varieties were attacked by the snoutbeetle. The mostly affected were Princeton, Optigree, and Midnight, with a damage index of 7.3, 7.2, and 6.8, respectively; the least affected variety was Conni, with a damage index of 1.3. At the end of the infestation also the most sensitive P. pratensis varieties, thanks to their enhanced rhizomatous capacity, managed to recolonize the open areas and make up for the serious aesthetic damage caused by the larvae of S. striatopunctatus.